Determinants of per-coital-act HIV-1 infectivity among African HIV-1-serodiscordant couples - Hughes, James P; Baeten, Jared M; Lingappa, Jairam R; Magaret, Amalia S; Wald, Anna; de Bruyn, Guy; Kiarie, James; Inambao, Mubiana; Kilembe, William; Farquhar, Carey; Celum, Connie (The Journal of infectious diseases, 2012)
Knowledge of factors that affect per-act infectivity of human immunodeficiency virus type 1 (HIV-1) is important for designing HIV-1 prevention interventions and for the mathematical modeling of the spread of HIV-1. We analyzed data from a prospective study of African HIV-1-serodiscordant couples. We assessed transmissions for linkage within the study partnership, based on HIV-1 sequencing. The primary exposure measure was the HIV-1-seropositive partners' reports of number of sex acts and condom use with their study partner. Of 3297 couples experiencing 86 linked HIV-1 transmissions, the unadjusted per-act risks of unprotected male-to-female (MTF) and female-to-male (FTM) transmission were 0.0019 (95% confidence interval [CI], .0010-.0037) and 0.0010 (95% CI, .00060-.0017), respectively. After adjusting for plasma HIV-1 RNA of the HIV-1-infected partner and herpes simplex virus type 2 serostatus and age of the HIV-1-uninfected partner, we calculated the relative risk (RR) for MTF versus FTM transmission to be 1.03 (P = .93). Each log(10) increase in plasma HIV-1 RNA increased the per-act risk of transmission by 2.9-fold (95% CI, 2.2-3.8). Self-reported condom use reduced the per-act risk by 78% (RR = 0.22 [95% CI, .11-.42]). Modifiable risk factors for HIV-1 transmission were plasma HIV-1 RNA level and condom use, and, in HIV-1-uninfected partners, herpes simplex virus 2 infection, genital ulcers, Trichomonas vaginalis, vaginitis or cervicitis, and male circumcision.